Characterizing Circulating Tumor Cells Isolated from Metastatic Breast Cancer Patients Using Graphene Oxide Based Microfluidic Assay. Issue 2 (25th October 2018) - Kim, Tae Hyun; Yoon, Hyeun Joong; Fouladdel, Shamileh; Wang, Yang; Kozminsky, Molly; Burness, Monika L.; Paoletti, Costanza; Zhao, Lili; Azizi, Ebrahim; Wicha, Max S.; Nagrath, Sunitha
Abstract: The enumeration of circulating tumor cells (CTCs) has shown prognostic importance in patients with breast cancer. However, CTCs are highly heterogeneous with diverse functional properties, which may also be clinically relevant. To provide a comprehensive landscape of the patient's disease, further CTC analysis is required. Here, a highly sensitive and reproducible graphene oxide based CTC assay is utilized to isolate and characterize CTCs from 47 metastatic breast cancer patients. The CTCs are captured with high purity, requiring only a few milliliters of blood and enabling efficient enumeration and subsequent analysis at both the protein and the transcription level. The results show that patient clinical outcomes correlate with the associated CTC profile and clearly demonstrate the potential use of the assay in the clinical setting. Collectively, these findings suggest that beyond simple enumeration, CTC characterization may provide further information that improves the diagnosis of the patients' disease status for proper treatment decisions. Moreover, this thorough validation study will facilitate the translation of the CTC assay into future clinical applications to broaden the utility of liquid biopsy. Abstract : A graphene oxide based circulating tumor cell (CTC) assay is reported presenting high sensitivity and purity for isolating CTCs from metastatic breast cancer patients. Captured CTCs are characterized for their expression at both the protein and transcription level and correlated to clinical outcomes. The results demonstrate the potential use of the assay for future clinical applications broadening the utility of liquid biopsy.